Basodo: Tradisi Pemberian Uang Kondangan pada Pasangan Pengantin - Ardila, Nike; Vera, Vety; Yuswalina; Areza, Chelsea Zia; Pranata, Eka Octavian; Smaradhani, Ika Indah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2025)
This study examines the tradition of giving wedding money to newlyweds, known locally as basodo, from the perspective of Islamic Economic Law. The practice, which has been passed down through generations in Ngulak Village, Sanga Desa District, reflects a social form of cooperation and solidarity among community members. However, differences in intention and purpose have led to two distinct legal understandings of the practice. Using a qualitative field research approach, data were collected through observation, interviews with community leaders and residents, and documentation of gift records. The findings reveal that the basodo tradition in Ngulak Village consists of two types of contracts. The first type, when given sincerely without expecting any return, is categorized as a hibah (grant). The second, when accompanied by an expectation of repayment during future social events, corresponds to a qardh (loan) contract. Both contracts are valid under Islamic law as long as they fulfill the pillars and conditions of mutual consent, sincerity, and absence of usury or coercion. Nevertheless, when the practice is influenced by social pressure or material expectation, it deviates from the Islamic principles of voluntarism (ikhlas) and mutual assistance (ta‘awun). Therefore, this study concludes that the basodo tradition remains permissible within Islamic Economic Law if carried out with sincere intention and willingness. The study also suggests strengthening community understanding of hibah and qardh concepts to ensure that customary practices continue to reflect the ethical and moral values of Islam.